The Influence of Future Orientation on Career Adaptability among Students of Universitas Muhammadiyah Papua - Buana, Yudha; Renaningtyas, Florensia (Indonesian Journal Publisher, 2025)
This study aims to analyze the influence of future orientation on career adaptability among final-year students at Universitas Muhammadiyah Papua. A quantitative approach with an explanatory survey design was employed, involving 135 students selected through a proportionate stratified random sampling technique. The research instruments included the Future Orientation Scale (α = 0.872) and the Career Adaptability Scale (α = 0.896), both of which demonstrated acceptable construct validity (factor loadings ranging from 0.62 to 0.84). Classical assumption tests indicated normally distributed data (p = 0.200), no multicollinearity (VIF < 2), and no heteroscedasticity (Sig. > 0.05). Data were analyzed using Structural Equation Modeling–Partial Least Squares (SEM-PLS). The results revealed a positive and significant effect of future orientation on career adaptability (β = 0.67; t = 9.458; p < 0.001), with an R² value of 0.45, indicating that future orientation explained 45% of the variance in career adaptability. Descriptive statistics showed a high level of future orientation (M = 82.45; SD = 7.68) and career adaptability (M = 79.12; SD = 6.94). These findings suggest that students with a stronger future orientation tend to demonstrate greater adaptability to career challenges. The results support Career Construction Theory and highlight the importance of developing future-oriented career guidance and training programs to enhance students’ professional readiness in a rapidly changing labor market)